On Finite-Time Feedback Control for Switched Discrete-Time Systems under Fast and Slow Switching. (24th December 2014) - Xiao, Liaoliang; Yu, Mingyang
Abstract : The problem of finite-time stabilization for switched discrete-time systems under both fast and slow switching is addressed. In the fast switching case, the designed static state feedback controller combines controllers for each subsystem and resetting controller at switching instant, it is shown that the resetting controller can reduce the conservativeness on controller design. Then the results are extended to output feedback controller design. Under slow switching, both static state feedback and output feedback controller are designed with admissible average dwell time, respectively. Several numerical examples are given to illustrate the proposed results within this paper.